Role of surface structures on long term stability of adhesive joints between Ti–15V–3Cr–3Sn–3Al and polyether-ether-ketone. (January 2023) - Löbbecke, Miriam; Bayerbasi, Tolga J.; Bartsch, Marion; Haubrich, Jan
Abstract: Adhesive bonding of similar and dissimilar materials is a key enabler for lightweight design in the automobile as well as aerospace industries. The strength and durability of adhesive metal-polymer joints in humid atmospheres depends strongly on surface pretreatments. Different pretreatments of Ti–15V–3Cr–3Sn–3Al (Ti15-3) for joining to polyether-ether-ketone (PEEK) were investigated in order to optimize the joint properties and elucidate underlying bonding mechanisms. Micro- and nanostructured surfaces were created with laser and chemical pretreatments and characterized with microscopy and X-ray photoelectron spectroscopy (XPS). The mechanical performance of the joints was analyzed with single lap shear tests in both the initial condition and after hydrothermal aging. Without significant structuring only physico-chemical interactions were present that accounted for strengths of up to 45 MPa. In the presence of micro- or nanostructures that add interlocking possibilities to the bonding, a maximum strength of 74 MPa was obtained. Hydrothermal aging resulted in poor residual strengths for samples without structuring, showing that humidity strongly degraded physico-chemical bonding. High aging resistance was particularly reached for laser pretreated specimens with an open-porous nanostructure. By comparing the different surfaces, it was found that (i) nanostructuring has a bigger impact on the aging resistance than microstructuring, and (ii) aging can be assigned mainly to weakening of physico-chemical bonding. Therefore, it can be deduced that nanomechanical interlocking is a key for producing long-term stable Ti15-3/PEEK joints. Highlights: particular surface morphology crucial for bonding performance. Nanostructuring is significantly more effective than structuring at the μm-level. Open-porous, branched nanostructure needed for strong nanomechanical interlocking. Strength reduction due to aging mainly caused by degradation of chemical bonds. Pulsed laser treatment a suitable technology for generating effective nanostructure.